Grassroots Planning Towards Institutionalization: A Case Study of Madhya Pradesh - Yogesh Mahor and Ram Gopal Singh (KILA Journal of Local Governance, 2013)
For the first time in Madhya Pradesh development history, the state government has accorded role of communities in making village-level development plans. The Madhya Pradesh State Planning Commission has formulated guideline for working more closely with communities. This paper outlines the nature of this initiative and analyses the adequacy of the framework for decentralisation adopted by the state government for achieving the desirable goal of state government for achieving the desirable goal of participatory democracy. It also presents the status of village-level planning in the state.